Repeated evolution of a morphological novelty: A phylogenetic analysis of the inflated fruiting calyx in the Physalideae tribe (Solanaceae) - Deanna, Rocío (2019)
The evolution of novel fruit morphologies has been integral to the success of angiosperms. The inflated fruiting calyx, in which the balloon-like calyx swells to completely surround the fruit, has evolved repeatedly across angiosperms and is postulated to aid in protection and dispersal. We investigated the evolution of this trait in the tomatillos and their allies (Physalideae, Solanaceae). METHODS: The Physalideae phylogeny was estimated using four regions (ITS, LEAFY, trnL-F, waxy) with maximum likelihood (ML) and Bayesian inference. Under the best-fitting ML model of trait evolution, we estimated ancestral states along with the numbers of gains and losses of fruiting calyx accrescence and inflation with Bayesian stochastic mapping. Also, phylogenetic signal in calyx morphology was examined with two metrics (parsimony score and Fritz and Purvis?s D).KEY RESULTS: Based on our well-resolved and densely sampled phylogeny, we infer that calyx evolution has proceeded in a stepwise and directional fashion, from non-accrescent to accrescent to inflated. In total, we inferred 24 gains of accrescence, 24 subsequent transitions to a fully inflated calyx, and only two reversals. Despite this lability, fruiting calyx accrescence and inflation showed strong phylogenetic signal. Our phylogeny greatly improves the resolution of Physalideae and highlights the need for taxonomic work. The comparative analyses reveal that the inflated fruiting calyx has evolved many times and that the trajectory toward this phenotype is generally stepwise and irreversible. These results provide a strong foundation for studying the genetic and developmental mechanisms responsible for the repeated origins of this charismatic fruit trait.